2022
DOI: 10.1159/000522425
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Ductal Adenocarcinoma: New Insights into the Actions of Vitamin A

Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is a gland-forming malignancy arising in the pancreas. It is estimated that in developed countries the incidence of PDAC will continue to rise, and PDAC is now the fourth leading cause of cancer-related deaths in the USA. The mortality of PDAC patients closely parallels the incidence rate, as this malignancy generally remains asymptomatic until it reaches an advanced stage. Summary: The poor prognosis results from the aggressive nature of the tumor, late de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Older studies report a lack of vitamin A in patients with PaC both associated with carcinomas in metastatic form, which then cause malabsorption [51] and pancreatic carcinoid syndrome [52]. A recent review evaluated the dysregulation of the functions of vitamin A (retinol) and its metabolites (retinoids) in PDAC and described their actions to support the development of new therapies and increase patient survival [53]. However, multiple factors, including nutritional components and individual-specific variable patterns, may play a role but are not exclusive predictors of PaC progression.…”
Section: Vitamin Amentioning
confidence: 99%
“…Older studies report a lack of vitamin A in patients with PaC both associated with carcinomas in metastatic form, which then cause malabsorption [51] and pancreatic carcinoid syndrome [52]. A recent review evaluated the dysregulation of the functions of vitamin A (retinol) and its metabolites (retinoids) in PDAC and described their actions to support the development of new therapies and increase patient survival [53]. However, multiple factors, including nutritional components and individual-specific variable patterns, may play a role but are not exclusive predictors of PaC progression.…”
Section: Vitamin Amentioning
confidence: 99%
“…This suggests a possible important role of ATRA in ADM (ref. 17,19 ). b) Pancreatic stellate cells (PSCs) -the retinol storing mesenchymal-like cells -have been described as an important part of the PDAC stroma interplay.…”
Section: Retinol and Atra In Pdacmentioning
confidence: 99%
“…It is also used 'off label' for nonsmall cell lung cancer and breast cancer (Esteva et al 2003, Dragnev et al 2007. In addition, a recent phase 1 clinical trial has shown that at-RA is a potent stromal targeting agent in pancreatic cancer and is now entering phase 2 status (Kocher et al 2020, Mere Del Aguila et al 2022.…”
Section: Rars and Cancermentioning
confidence: 99%